Temperature-Independent Rescaling of the Local Activation Barrier Drives Free Surface Nanoconfinement Effects on Segmental-Scale Translational Dynamics near T g - Diaz-Vela, Daniel; Hung, Jui-Hsiang; Simmons, David S (ACS macro letters, 2018)
Near-interface alterations in dynamics and glass formation behavior have been the subject of extensive study for the past two decades, both because of their practical importance and in the hope of revealing underlying correlation lengths underpinning glass transition more generally. Here we employ molecular dynamics simulations of thick films to demonstrate that these effects emerge, for segmental-scale translational dynamics at low temperature, from a temperature-independent rescaling of the local activation barrier. This rescaling manifests as a fractional power law decoupling relationship of local dynamics relative to the bulk, with a transition from a regime of weak decoupling at high temperatures to a regime of strong decoupling at low temperatures. The range of this effect saturates at low temperatures, with 90% of the surface perturbation in the barrier lost over a range of 12 segmental diameters. These findings reduce the phenomenology of T g nanoconfinement effects to two propertiesa position-dependent, temperature independent, barrier rescaling factor and an onset time scalewhile substantially constraining the predictions required from any theoretical explanation of this phenomenon.